STRUKTUR KOMUNITAS KAWASAN MANGROVE DI DESA TALENGEN KECAMATAN TABUKAN TENGAH KABUPATEN KEPULAUAN SANGIHE (JURNAL PESISIR DAN LAUT TROPIS, 2022)
Mangroves are vegetation that grows on the tidal area and can grow on muddy, sandy and mix substrates. The purpose of this study was to determine the type, community structure, measure the diameter of mangrove trees, and mangrove community structures data. The data was taken using the line transect quadrat method. The results of the study found that there were three types of mangroves, namely Rhizophora mucronata, Bruguiera gymnorrhiza and Sonneratia alba. The highest species density and the highest relative belong to R. mucronata 0.11 Ind/m2 and 75.71% respectively. The highest value of frequency and relative frequency was found on mucronata with a value of 1.00 and a relative 62.50%. The highest species cover value wasfound on B.gymnorrhizawith a value of 20.04 cm2/ha and relative cover 63.24%. The highest important Value Index belongs to R. mucronata with a value of 234.70%. The diversity index value with a value of 0.68 is included in the low category because H'